Electroluminescent device and display device including the same
Through the mixed structure of the inorganic nanoparticle cluster layer and the high-work function organic layer, the problems of charge carrier balance and light extraction efficiency in electroluminescent devices are solved, excellent driving characteristics and life characteristics are achieved, and leakage current is reduced.
Patent Information
- Application Number
- CN201910184028.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-03-12
- Filing Date
- 2019-03-12
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2039-03-12
AI Technical Summary
While improving the charge carrier balance and light extraction efficiency of the emitting layer, existing electroluminescent devices are difficult to minimize leakage current, affecting the luminous efficiency and lifetime.
Using a mixed structure of a cluster layer composed of inorganic nanoparticles and an organic layer with high work function, as an electron transport layer, the charge carrier equilibrium and light extraction efficiency are improved by alternate stacking of the cluster layer and the organic layer of the inorganic layer, and the charge carrier equilibrium and light extraction efficiency are improved, and The organic layer covers the surface of the inorganic layer to reduce leakage current.
Excellent driving characteristics and life characteristics are achieved, the luminous efficiency of the emitting layer is improved, and the leakage current is significantly reduced, which improves the overall performance of the device.
Smart Images

Figure CN110265555B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-0028836 filed in the Korean Intellectual Property Office on March 12, 2018, the entire contents of which are incorporated herein by reference. Technical Field
[0003] Disclosed are an electroluminescent device and a display device including the same. Background Art
[0004] Quantum dots are nanocrystalline semiconductor materials with a particle size of about several nanometers to several hundred nanometers that show a quantum confinement effect. Compared with conventional phosphors, quantum dots produce stronger light in a narrower wavelength region. Quantum dots emit light when excited electrons transition from the conduction band to the valence band, and even in the same material, the wavelength varies depending on the particle size. Since for quantum dots, the smaller the particle size, the shorter the wavelength of the emitted light, they can obtain light in a desired wavelength region by adjusting the size.
[0005] Since desired colors can be emitted by changing the size of quantum dots without using other materials (such as organic materials) in the emission layer to emit light of other colors, emission layers including quantum dots and various electronic devices including the same can generally save production costs compared to emission layers including phosphorescent and / or fluorescent materials.
[0006] The luminous efficiency of the emission layer including quantum dots is determined by the external quantum efficiency of the quantum dots, the balance of charge carriers, the light extraction efficiency, etc. Therefore, when the emission layer including quantum dots is applied as an electroluminescent layer, the balance of charge carriers and the light extraction efficiency need to be improved and the leakage current needs to be minimized to improve the luminous efficiency of the emission layer. Summary of the invention
[0007] Provided is an electroluminescent device capable of minimizing leakage current while improving charge carrier balance and light extraction efficiency of an emission layer.
[0008] According to one embodiment, an electroluminescent device includes a first electrode and a second electrode facing each other; an emission layer disposed between the first electrode and the second electrode and including a plurality of light-emitting particles; a hole transport layer disposed between the first electrode and the emission layer; and an electron transport layer disposed between the emission layer and the second electrode, wherein the electron transport layer includes an inorganic layer disposed on the emission layer and including a plurality of inorganic nanoparticles; and an organic layer directly disposed on the inorganic layer and having a higher work function than the inorganic layer.
[0009] The organic layer may completely cover a surface of the inorganic layer opposite to a surface thereof close to the emission layer (ie, a surface of the inorganic layer far from the emission layer, hereinafter, referred to as an upper surface).
[0010] The organic layer may have a LUMO (Lowest Unoccupied Molecular Orbital) energy level of about −2.8 eV to about −1.8 eV.
[0011] The organic layer may have about 10 -3 cm 2 / V·s-about 10 -1 cm 2 / V·s electron mobility.
[0012] The inorganic nanoparticles may include ZnO, TiO 2 、ZrO 2 SnO 2 , WO 3 、 2 O 3 , or a combination thereof.
[0013] The inorganic nanoparticles may have an average particle diameter of less than or equal to about 100 nm.
[0014] The inorganic layer may include a cluster layer composed of the inorganic nanoparticles.
[0015] The cluster layer may be disposed directly on the emitting layer.
[0016] The surface of the cluster layer opposite to the surface thereof contacting the emission layer (i.e., the surface of the cluster layer away from the emission layer, hereinafter referred to as the upper surface) may include two or more grains composed of the inorganic nanoparticles and grain boundaries formed between adjacent grains, and the organic layer may fill at least a portion of the grain boundaries.
[0017] The organic layer may include a quinolone-based compound, a triazine-based compound, a quinoline-based compound, a triazole-based compound, a naphthalene-based compound, or a combination thereof.
[0018] The organic layer may include at least two different organic semiconductor compounds.
[0019] The organic layer may include first and second organic semiconductor compounds different from each other and a weight ratio of the first and second organic semiconductor compounds in the organic layer may be about 3:7 to about 7:3.
[0020] The organic layer may have an average thickness of about 2 nm to about 20 nm.
[0021] The inorganic layer and the organic layer may be alternately stacked two or more times.
[0022] The luminescent particles may include quantum dots.
[0023] The quantum dots may include: Group II-VI compounds excluding Cd, Group III-V compounds, Group IV-VI compounds, Group IV elements or compounds, Group I-III-VI compounds, Group I-II-IV-VI compounds excluding Cd, or combinations thereof.
[0024] The quantum dots may have a core-shell structure.
[0025] The electron transport layer may not have electroluminescent properties.
[0026] According to another embodiment, a display device includes the electroluminescent device.
[0027] An electroluminescent device having excellent driving characteristics and lifespan characteristics by improving charge carrier balance and light extraction efficiency of an emission layer and simultaneously minimizing leakage current, and a display apparatus including the same can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 is a schematic cross-sectional view of an electroluminescent device according to an embodiment,
[0029] Figure 2 To show a microscope image of the upper surface of the inorganic layer of the electroluminescent device according to the embodiment,
[0030] Figure 3 To show a three-dimensional morphology (topography) image of the upper surface of the inorganic layer of the electroluminescent device according to the embodiment measured using a Zygo interferometer and a graph of height deviation depending on position,
[0031] Figure 4 is an energy band diagram of an electroluminescent device according to an embodiment,
[0032] Figure 5-7 are graphs showing IVL characteristics of the electroluminescent devices according to Example 1 and Comparative Examples 1-3; respectively, Figure 5 Display voltage-current density, Figure 6 Display voltage-brightness, and Figure 7 Display brightness - external quantum efficiency (EQE),
[0033] Figure 8 is a graph showing the voltage-current density relationship of the electroluminescent devices according to Example 1 and Comparative Examples 1-3,
[0034] Fig. 9is a time-brightness diagram of the electroluminescent device according to Example 2, Comparative Example 1, and Comparative Example 2,
[0035] Figure 10-12 are graphs showing IVL characteristics of the electroluminescent devices according to Example 3 and Comparative Example 4; respectively, Fig.10 Display voltage-current density, Fig.11 Display voltage-brightness, and Fig.12 Display brightness - external quantum efficiency, and
[0036] Fig.13 3 is a voltage-current density diagram of the electroluminescent devices according to Example 3 and Comparative Example 4. DETAILED DESCRIPTION
[0037] Example embodiments of the present disclosure will be described in detail below and can be easily made by those having ordinary knowledge in the relevant field. However, the present disclosure can be embodied in many different forms and should not be construed as limited to the example embodiments set forth herein.
[0038] In the accompanying drawings, the thickness of layers, films, panels, regions, etc., is exaggerated for clarity. The same reference numerals represent the same elements throughout the specification. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on the other element or there may be intermediate elements. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements.
[0039] In the embodiment, for the sizes or particle diameters of various particles, although they can be calculated (numerized) by measurement to show the average size of a group, methods generally used include a mode diameter showing the maximum value of the distribution, a median diameter corresponding to the central value of the integrated distribution curve, a variety of average diameters (number average, length average, area average, mass average, volume average, etc.), etc. Unless otherwise specifically mentioned, the average size or average particle diameter herein means the number average size or number average diameter, and it is obtained by measuring D50 (particle diameter at the position of 50% of the distribution rate).
[0040] As used herein, a "Group" may refer to a Group of the periodic table.
[0041] As used herein, “Group II” may refer to Group IIA and Group IIB, and examples of Group II metals may be Cd, Zn, Hg, and Mg, but are not limited thereto.
[0042] As used herein, “Group II metal excluding Cd” may refer to Group II metals other than Cd, such as Zn, Hg, Mg, and the like.
[0043] As used herein, “Group III” may refer to Group IIIA and Group IIIB, and examples of Group III metals may be Al, In, Ga, and Tl, but are not limited thereto.
[0044] As used herein, "Group IV" may refer to Group IVA and Group IVB, and examples of Group IV metals may be Si, Ge, and Sn, but are not limited thereto. As used herein, "metal" may include semimetals such as Si.
[0045] As used herein, “Group I” may refer to Group IA and Group IB, and examples may include Li, Na, K, Ru, and Cs, but are not limited thereto.
[0046] As used herein, “Group V” may refer to Group VA, and examples may include nitrogen, phosphorus, arsenic, antimony, and bismuth, but are not limited thereto.
[0047] As used herein, “Group VI” may refer to Group VIA, and examples may include sulfur, selenium, and tellurium, but are not limited thereto.
[0048] Hereinafter, the work function (WF), the highest occupied molecular orbital (HOMO) energy level, and the lowest unoccupied molecular orbital (LUMO) energy level are expressed as absolute values from the vacuum energy level (i.e., 0 electron volts (eV)). In addition, when the work function, HOMO energy level, or LUMO energy level is referred to as "deep", "high", or "large", the work function or HOMO energy level has a larger absolute value from the vacuum energy level (0 eV), and when the work function, HOMO energy level, or LUMO energy level is "shallow", "low", or "small", the work function or HOMO energy level has a smaller absolute value from the vacuum energy level (0 eV).
[0049] First, refer to Figure 1 , describing a schematic structure of an electroluminescent device according to an embodiment.
[0050] Figure 1 is a schematic cross-sectional view of an electroluminescent device according to an embodiment.
[0051] The electroluminescent device 10 according to the embodiment includes a first electrode 110 and a second electrode 160 facing each other, an emission layer 140 disposed between the first electrode 110 and the second electrode 160 and including a plurality of light-emitting particles 141, a hole transport layer 130 disposed between the first electrode 110 and the emission layer 140, and an electron transport layer 150 disposed between the emission layer 140 and the second electrode 160.
[0052] The electroluminescent device 10 according to the embodiment supplies current to the emission layer 140 including the light emitting particles 141 through the first electrode 110 and the second electrode 160 and causes electroluminescence of the light emitting particles 141 to generate light. The electroluminescent device 10 can generate light in different wavelength regions according to the material, size, or fine structure of the light emitting particles 141 of the emission layer 140.
[0053] In one embodiment, the first electrode 110 may be directly connected to a driving power source, and thus may function to allow current to flow to the emission layer 140. The first electrode 110 may include a material having light transmittance in at least the visible light wavelength region, but is not limited thereto. The first electrode 110 may include a material having light transmittance in the infrared or ultraviolet (UV) wavelength region. For example, the first electrode 110 may be made of an optically transparent material.
[0054] In one embodiment, the first electrode 110 may include molybdenum oxide, tungsten oxide, vanadium oxide, rhenium oxide, niobium oxide, tantalum oxide, titanium oxide, zinc oxide, nickel oxide, copper oxide, cobalt oxide, manganese oxide, chromium oxide, indium oxide, or a combination thereof.
[0055] Meanwhile, in one embodiment, the first electrode 110 may be disposed on the substrate 100, such as Figure 1 As shown in . The substrate 100 may be a transparent insulating substrate or may be made of a ductile material. The substrate 100 may include glass or a polymer material in the form of a film having a glass transition temperature (Tg) greater than about 150° C. For example, it may include a material based on COC (cyclic olefin copolymer) or COP (cyclic olefin homopolymer).
[0056] In one embodiment, the substrate 100 supports the hole transport layer 130, the emission layer 140, and the electron transport layer 150 sandwiched by the first electrode 110 and the second electrode 160. However, the first electrode 110 of the electroluminescent device 10 according to the embodiment is not necessarily provided on the substrate 100, and the substrate may be provided on the second electrode 160 or may be omitted as needed.
[0057] The second electrode 160 includes an optically transparent material and may function as a light-transmitting electrode for transmitting light generated in the emission layer 140, which will be described later. In one embodiment, the second electrode 160 may include at least one selected from the group consisting of silver (Ag), aluminum (Al), copper (Cu), gold (Au), and alloys thereof, molybdenum oxide, tungsten oxide, vanadium oxide, rhenium oxide, niobium oxide, tantalum oxide, titanium oxide, zinc oxide, nickel oxide, copper oxide, cobalt oxide, manganese oxide, chromium oxide, indium oxide, or a combination thereof.
[0058] Each of the first electrode 110 and the second electrode 160 may be formed by depositing a material for forming an electrode on the substrate 100 or an organic layer 153 described later by a method such as sputtering.
[0059] The emission layer 140 may include a plurality of light emitting particles 141. The emission layer 140 may be formed by applying a resin in which the plurality of light emitting particles 141 are dispersed on the hole transport layer 130 described later and curing it.
[0060] The emission layer 140 is a place where electrons and holes transferred by current supplied from the first and second electrodes 110 and 160 recombine to generate excitons, and the generated excitons transition from an excited state to a ground state to emit light of a wavelength corresponding to the size of the light emitting particle 141 .
[0061] In an implementation, the light emitting particles 141 may include quantum dots.
[0062] The quantum dots have a discontinuous energy band gap due to a quantum confinement effect. That is, when the emission layer 140 includes the quantum dots as the light emitting particles 141, the emission layer 140 may generate light having excellent color reproducibility and color purity.
[0063] In an embodiment, the material of the quantum dot is not particularly limited and known or commercially available quantum dots can be used. For example, the quantum dot may include: a II-VI compound, a III-V compound, a IV-VI compound, a IV element or compound, a I-III-VI compound, a I-II-IV-VI compound not including Cd, or a combination thereof. The quantum dot according to an embodiment may be a non-cadmium-based quantum dot. In this way, when the quantum dot is composed of a non-cadmium-based material, it is non-toxic compared to conventional cadmium-based quantum dots and is therefore non-hazardous and environmentally friendly.
[0064] The II-VI group compound may be selected from: a binary compound selected from ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, and mixtures thereof; a ternary compound selected from ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, and mixtures thereof; and a quaternary compound selected from HgZnTeS, HgZnSeS, HgZnSeTe, HgZnSTe, and mixtures thereof. The II-VI group compound may further include a group III metal.
[0065] The III-V compound may be selected from: a binary compound selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, and a mixture thereof; a ternary compound selected from GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, InZnP, and a mixture thereof; and a quaternary compound selected from GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, and a mixture thereof. The III-V compound may further include a Group II metal (e.g., InZnP).
[0066] The IV-VI group compound may be selected from: a binary compound selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, and mixtures thereof; a ternary compound selected from SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, and mixtures thereof; and a quaternary compound selected from SnPbSSe, SnPbSeTe, SnPbSTe, and mixtures thereof. Examples of the I-III-VI group compound may be CuInSe 2 、CuInS 2 , CuInGaSe, and CuInGaS, but not limited thereto. Examples of the I-II-IV-VI group compound may be CuZnSnSe and CuZnSnS, but not limited thereto. Examples of the IV group element or compound may be a simple substance selected from Si, Ge, and a mixture thereof; and a binary compound selected from SiC, SiGe, and a mixture thereof.
[0067] The binary compound, ternary compound or quaternary compound is present in each case in a uniform concentration in the particles or in locally different concentrations in the same particle.
[0068] According to one embodiment, the quantum dot may have a core-shell structure including a semiconductor nanocrystal core and another semiconductor nanocrystal shell surrounding the core. The core and the shell may have a concentration gradient in which the concentration of one or more elements of the shell decreases toward the core. In addition, the quantum dot may have a semiconductor nanocrystal core and a multilayer shell surrounding the core. Here, the multilayer shell structure has a structure of two or more shells and each shell may have a single composition (ingredient) or an alloy or may have a concentration gradient.
[0069] When the quantum dot according to the embodiment has a core-shell structure, the material composition of the shell has a larger band gap than the band gap of the core, which can present an effective quantum confinement effect. However, the embodiment is not limited thereto. At the same time, in the multi-layer shell, the shell farther from the core may have a higher band gap than the shell closer to the core and the quantum dot may emit light in the ultraviolet (UV) to infrared wavelength range.
[0070] The quantum dots may have an external quantum efficiency (EQE) of greater than or equal to about 10%, such as greater than or equal to about 30%, greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 90%, or even 100%.
[0071] In a display, the quantum dots may have a relatively narrow emission spectrum to improve color purity or color reproducibility. The quantum dots may have, for example, a half width (FWHM) of a wavelength spectrum of less than or equal to about 45 nm, less than or equal to about 40 nm, or less than or equal to or about 30 nm. Within the range, the color purity or color reproducibility of the device may be improved.
[0072] The quantum dots may have an average particle diameter of about 1 nm to about 100 nm (the longest dimension for non-spherical shaped particles). For example, the quantum dots may have an average particle diameter of about 1 nm to about 20 nm, such as about 2 nm (or about 3 nm) to about 15 nm.
[0073] In addition, the shape of the quantum dot particles can be a common shape in the art and therefore may not be particularly limited. For example, the quantum dot particles may have a spherical, elliptical, tetrahedral, pyramidal, cuboctahedral, cylindrical, polyhedral, multi-arm, or cubic shape, and may be a nanoparticle, nanotube, nanowire, nanofiber, nanosheet, or a combination thereof. The quantum dot may have any cross-sectional shape.
[0074] The quantum dots may be commercially available or may be synthesized by any method. For example, quantum dots of a few nanometers in size may be synthesized according to a wet chemical process. In a wet chemical process, a precursor reacts in an organic solvent to grow crystalline particles, and the organic solvent or ligand compound may coordinate to the surface of the quantum dots to control the growth of the crystal. Examples of the organic solvent and the ligand compound are known. The organic solvent coordinated on the surface of the quantum dots may affect the stability of the device, and therefore, the excess organic material that is not coordinated on the surface of the nanocrystal may be removed by pouring it into an excess of a non-solvent and centrifuging the resulting mixture. Examples of the non-solvent may be acetone, ethanol, methanol, etc., but are not limited thereto. After removing the excess organic material, the amount of the organic material coordinated on the surface of the quantum dots may be less than or equal to about 50% by weight, such as less than or equal to about 30% by weight, less than or equal to about 20% by weight, or less than or equal to about 10% by weight, based on the weight of the quantum dots. The organic material may include a ligand compound, an organic solvent, or a combination thereof.
[0075] The quantum dots may have, for example, organic ligands having a hydrophobic portion bound to their surface. In one embodiment, the organic ligands having a hydrophobic portion may be RCOOH, RNH 2 , R 2 NH, R 3 N, RSH, R 3 PO, R 3 P, ROH, RCOOR', RPO(OH) 2 , R 2 POOH (wherein, R and R' are independently C5-C24 alkyl, C5-C24 alkenyl, C5-C20 alicyclic group, or C6-C20 aryl), a polymeric organic ligand, or a combination thereof. The organic ligand may be a monofunctional organic ligand and the functional group may be bound to the surface of the quantum dot.
[0076] In one embodiment, the hole transport layer 130 may be disposed between the first electrode 110 and the emission layer 140. The hole transport layer 130 may transport holes into the emission layer 140.
[0077] The electroluminescent device 10 according to the embodiment may further include a hole injection layer 120 between the hole transport layer 130 and the first electrode 110. The hole injection layer 120 supplies holes to the hole transport layer 130.
[0078] The hole injection layer 120 and the hole transport layer 130 may each include, for example, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS), poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB), polyarylamine, poly(N-vinylcarbazole), polyaniline, polypyrrole, N,N,N',N'-tetrakis(4-methoxyphenyl)-benzidine (TPD), 4-bis[N-(1-naphthyl)-N-phenyl-amino]biphenyl (α-NPD), m-MTDATA (4,4,4"-tri[phenyl(m-tolyl)amino]triphenylamine), 4,4',4"-tri(N-carbazolyl)-triphenylamine (TCTA), 1,1-bis[(di-4-tolylamino)phenyl]cyclohexane (TAPC), and combinations thereof, but are not limited thereto. Depending on the internal energy level of the electroluminescent device 10, different semiconductor materials, or combinations thereof, may be applied.
[0079] The hole injection layer 120 and the hole transport layer 130 according to the embodiment may be formed by coating a commercially available solution type material on the first electrode 110 and then curing it, but is not limited thereto.
[0080] In one embodiment, the electron transport layer 150 is disposed between the emission layer 140 and the second electrode 160 and transports electrons into the emission layer 140 .
[0081] The electron transport layer 150 according to the embodiment may be composed of a non-luminescent charge transport material that does not emit light due to an electric field. Thus, internal light emission of the electroluminescent device 10 according to the embodiment occurs in the emission layer 140 rather than in the electron transport layer 150.
[0082] The electron transport layer 150 according to an embodiment may include an inorganic layer 151 formed on the emission layer 140 and including a plurality of inorganic nanoparticles 152 (ie, two or more inorganic nanoparticles), and an organic layer 153 formed directly on the inorganic layer 151 on a side opposite to the emission layer 140 .
[0083] like Figure 1 As shown in , the inorganic layer 151 may be directly formed on the emission layer 140 .
[0084] The inorganic layer 151 may include a plurality of inorganic nanoparticles 152 and the plurality of inorganic nanoparticles 152 may be agglomerated with each other to form a cluster layer. In one embodiment, the inorganic layer 151 may be a cluster layer composed of the plurality of inorganic nanoparticles 152.
[0085] In the case where the cluster layer composed of the plurality of inorganic nanoparticles 152 is directly on the emission layer 140 , non-emissive quenching of charge exchange excitons generated in the emission layer 140 may be prevented, and the brightness of the emission layer 140 may be improved.
[0086] The inorganic nanoparticles 152 according to an embodiment may include ZnO, TiO 2 、ZrO 2 SnO 2 , WO 3 、 2 O 3 , or inorganic oxide nanoparticles of a combination thereof, but not limited thereto.
[0087] In the case where the cluster layer is made of, for example, inorganic oxide nanoparticles, the emission layer 140 including non-cadmium quantum dots generates a large amount of charge exchange excitons due to internal heat generation during the driving of the device, and the generated charge exchange excitons can emit Auger electrons at the interface with the cluster layer through the cluster layer without non-emission quenching. The emitted Auger electrons can emit light by recombining with holes in the emission layer 140, and the roll-off of the electroluminescent device 10 in the high brightness region can be minimized.
[0088] On the other hand, the average particle diameter of the inorganic nanoparticles 152 according to the embodiment (for particles with non-spherical shapes, the diameter means the longest dimension) may be, for example, less than or equal to about 150 nm, less than or equal to about 140 nm, less than or equal to about 130 nm, less than or equal to about 120 nm, less than or equal to about 110 nm, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, less than or equal to about 40 nm, less than or equal to about 30 nm, less than or equal to about 20 nm, or less than or equal to about 10 nm and, for example, greater than or equal to about 1 nm, greater than or equal to about 2 nm, greater than or equal to about 3 nm, greater than or equal to about 4 nm, or greater than or equal to about 5 nm.
[0089] When the inorganic layer 151 is a cluster layer composed of a plurality of inorganic nanoparticles 152 as described above, its electron mobility is much higher than that of a common inorganic semiconductor film or an organic semiconductor film. Therefore, the luminescence stability and brightness of the non-cadmium quantum dots can be improved by the cluster layer used in the inorganic layer 151.
[0090] In addition, the average thickness of the cluster layer according to an embodiment may be, for example, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, less than or equal to about 60 nm, less than or equal to about 50 nm, or less than or equal to about 40 nm and, for example, greater than or equal to about 10 nm, greater than or equal to about 15 nm, greater than or equal to about 20 nm, greater than or equal to about 25 nm, or greater than or equal to about 30 nm.
[0091] When the average particle diameter of the inorganic nanoparticles 152 and the average thickness of the cluster layer are within the above ranges, the inorganic layer 151 may exhibit excellent electron mobility.
[0092] Figure 2 A microscope image showing the upper surface of the inorganic layer of the electroluminescent device according to the embodiment and Figure 3 FIG. 1 is a diagram showing a three-dimensional morphological image of an upper surface of an inorganic layer of an electroluminescent device according to an embodiment measured using a Zygo interferometer and a height deviation depending on a position.
[0093] Figure 2 and 3 This corresponds to the case where a cluster layer having a thickness of about 40 nm is formed by agglomerating ZnO nanoparticles having an average particle diameter of 3 nm.
[0094] First, refer to Figure 2 It can be seen that the surface of the cluster layer includes two or more grains composed of inorganic nanoparticles 152 and grain boundaries formed between adjacent grains.
[0095] In addition, refer to Figure 3 , showing a surface roughness curve of the straight line portion shown in the surface profile image of the cluster layer, the peak-to-valley (PV) value of the surface of the cluster layer is 16.343 nm and the root mean square roughness (Rq) calculated by the root mean square (rms) method is 1.914 nm.
[0096] Therefore, now refer to Figure 1, the surface region 151a of the cluster layer according to the embodiment may present an uneven surface morphology, which may be caused by uneven agglomeration of inorganic nanoparticles 152a in the surface region 151a, variation in particle size of inorganic nanoparticles 152a in the surface region 151a, detachment of inorganic nanoparticles 152a from the cluster layer, a combination thereof, and the like, which results in the presence of grain boundaries in the surface region 151a. In some embodiments, the upper surface of the cluster layer includes the surface region 151a, and the surface region 151a has two or more grains each including inorganic nanoparticles, wherein grain boundaries are formed between adjacent grains. The inorganic nanoparticles in the surface region 151a may include the inorganic nanoparticles 152a. In other words, the inorganic nanoparticles 152a are inorganic nanoparticles of the plurality of nanoparticles not included in the cluster layer.
[0097] On the other hand, according to one embodiment, the organic layer 153 is directly formed on at least a portion of the inorganic layer 151. The organic layer 153 may be formed through a deposition process on the cluster layer of the inorganic nanoparticles 152, or the like.
[0098] The organic layer 153 is a layer composed of an organic semiconductor compound and may include a single molecule of conductivity, a low molecular organic material having a conjugated structure, or a combination thereof. Specific examples of the organic semiconductor compound forming the organic layer 153 may be a quinolone-based compound, a triazine-based compound, a quinoline-based compound, a triazole-based compound, a naphthalene-based compound, or a combination thereof, but are not limited thereto. In some embodiments, the organic semiconductor compound may be a phosphine oxide-based compound (NET-218, Novaled Electron Transport material 218, obtained from Novaled), a phosphonophenol-based compound (NDN-87, Novaled Dopant n-side material 87, obtained from Novaled), or a combination thereof.
[0099] The organic layer 153 may be composed of an organic semiconductor compound having a work function higher than that of the inorganic layer 151. Therefore, the organic layer 153 may function as an energy barrier against electrons moving from the second electrode 160 to the inorganic layer 151.
[0100] The LUMO (lowest unoccupied molecular orbital) energy level of the organic layer 153 may be, for example, about -2.8 eV to about -1.8 eV, about -2.7 eV to about -1.8 eV, about -2.6 eV to about -1.8 eV, about -2.5 eV to about -1.8 eV, about -2.4 eV to about -1.8 eV, about -2.3 eV to about -1.8 eV, or about -2.2 eV to about -1.8 eV.
[0101] On the other hand, the organic layer 153 may have a thickness of, for example, greater than or equal to about 10 -4 cm 2 / V·s or greater than or equal to about 10 -3 cm 2 / V·s and, for example, less than or equal to about 1 cm 2 / V·s or less than or equal to about 10 -1 cm 2 / V·s electron mobility.
[0102] The organic layer 153 according to an embodiment completely covers the upper surface of the inorganic layer 151, so that the inorganic layer 151 may not be exposed toward the second electrode 160. Figure 1 In other words, the organic layer 153 is disposed on and in contact with the entire upper surface of the inorganic layer 151. Therefore, the organic layer 153 fills at least a portion or all of the grain boundaries formed at, on, or in the surface of the cluster layer in contact therewith (i.e., between the inorganic nanoparticles 152a in the surface region 151a).
[0103] On the other hand, the organic layer 153 may fill part or all of the cracks or voids generated by the detachment or uneven agglomeration of the inorganic nanoparticles 152a on the surface of the cluster layer in contact therewith. In some embodiments, the organic layer 153 is disposed on the upper surface of the inorganic layer 151 so that substantially all of the cracks, voids, grain boundaries, etc. on the upper surface are filled with or include the organic semiconductor compound of the organic layer 153.
[0104] The thickness of the organic layer 153 may be variously designed depending on the electron mobility, work function, etc. of the organic layer 153. It may be thin enough to at least transmit electrons to the inorganic layer 151 by tunneling, and it may be thick enough to fill the grain boundaries, cracks, and voids on the surface of the inorganic layer 151 and not expose but cover the inorganic layer 151.
[0105] In one embodiment, the thickness of the organic layer 153 may be, for example, less than or equal to about 20 nm, less than or equal to about 18 nm, less than or equal to about 16 nm, less than or equal to about 14 nm, less than or equal to about 12 nm, less than or equal to about 10 nm, less than or equal to about 8 nm, less than or equal to about 6 nm, or less than or equal to about 4 nm and, for example, greater than or equal to about 2 nm, greater than or equal to about 2.5 nm, or greater than or equal to about 3 nm.
[0106] Since the organic layer 153 has a higher work function than the inorganic layer 151, the driving voltage for transporting electrons may be slightly increased compared to the case where the inorganic layer is used alone as an electron transport layer. However, when the organic layer 153 according to an embodiment has a LUMO energy level and electron mobility within the range and further has a thickness adjusted within the range, the driving voltage and electron mobility may be adjusted to have appropriate levels due to band bending and tunneling effects.
[0107] On the other hand, the organic layer 153 may include at least two different organic semiconductor compounds. The organic layer 153 according to the embodiment may be formed by a method of co-depositing at least two different organic semiconductor compounds, or the like.
[0108] For example, when any one of the organic semiconductor compounds is used, a plurality of island-shaped intermediates are formed due to uneven morphology on the surface of the inorganic layer 151 during formation of the organic semiconductor compound, and thus, the organic layer 153 may have a large thickness deviation. On the other hand, when at least two different organic semiconductor compounds are used, the organic layer 153 may have a relatively small thickness deviation.
[0109] In addition, the organic layer 153 may include two different organic semiconductor compounds (a first organic semiconductor compound and a second organic semiconductor compound).
[0110] Here, the first organic semiconductor compound and the second organic semiconductor compound in the organic layer 153 may be used in various weight ratios depending on the materials of each organic semiconductor compound, wherein the weight ratio may be adjusted to minimize (smallen) the formation of island-shaped intermediates.
[0111] In one implementation, the first organic semiconductor and the second organic semiconductor in the organic layer 153 may have a weight ratio of, for example, about 2:8 to about 8:2, about 3:7 to about 7:3, about 4:6 to about 6:4, or about 5:5.
[0112] On the other hand, the inorganic layer 151 and the organic layer 153 may be alternately stacked two or more times on the emission layer 140. In other words, the electron transport layer 150 may include at least two stack units consisting of the inorganic layer 151 and the organic layer 153. In this way, by considering the energy levels of the first electrode 110, the second electrode 160, the hole injection layer 120, the hole transport layer 130, and the emission layer 140, their energy level differences, etc., the number of alternately stacked inorganic layers 151 and organic layers 153 can be adjusted to appropriately maintain the charge carrier balance in the electroluminescent device.
[0113] On the other hand, when the cluster layer composed of inorganic nanoparticles is applied to the emission layer including quantum dots, the device efficiency at high brightness can be guaranteed, but since cracks, voids, grain boundaries, etc. on the surface of the cluster layer can, for example, act as leakage paths for current, the leakage current from the leakage paths can deteriorate the device efficiency at low voltage and in low brightness areas.
[0114] However, the electroluminescent device 10 according to the embodiment includes the organic layer 153 filling cracks, voids, grain boundaries, etc. on the surface of the cluster layer, and thus generation of leakage current due to the cluster layer may be minimized.
[0115] The electroluminescent device 10 according to the embodiment may further include an electron injection layer (not shown) between the second electrode 160 and the electron transport layer 150 and may further include an electron blocking layer (not shown) between the second electrode 160 and the electron injection layer (not shown) or between the electron injection layer (not shown) and the electron transport layer 150. However, the embodiment is not limited thereto, and in order to maintain the charge carrier balance of the electroluminescent device 10 at an appropriate level, the electron injection layer (not shown) and the electron blocking layer (not shown) may be omitted.
[0116] In the following, refer to Figure 4 , explaining the driving principle of the electroluminescent device according to the embodiment.
[0117] Figure 4 FIG. 2 is an energy band diagram showing an electroluminescent device according to an embodiment.
[0118] The electroluminescent device 10 according to the embodiment includes quantum dots as the light emitting particles 141 , and therefore, the emission layer 140 formed therefrom has an energy level different from that of a general organic light emitting diode.
[0119] Specifically, a general electroluminescent device sequentially transfers electrons from an electrode to an emission layer through an electron transport layer according to the LUMO energy level, but the electroluminescent device 10 according to the embodiment has an organic layer 153 having a LUMO energy level higher than that of the inorganic layer 151 and thus acting as a high energy barrier. Therefore, the electron transport layer 150 according to the embodiment has a hybrid structure composed of the inorganic layer 151 as a cluster layer formed of inorganic nanoparticles and the organic layer 153 covering the inorganic layer 151.
[0120] In one embodiment, when the cluster layer formed of inorganic nanoparticles is formed on the surface of the emission layer 140 including quantum dots, the cluster layer has an electron mobility much higher than the hole mobility between the hole injection layer (HIL) 120 and the hole transport layer (HTL) 130, and leakage current may be generated due to the uneven surface morphology of the cluster layer.
[0121] Therefore, in one embodiment, an organic layer 153 having a work function higher than that of the cluster layer may be formed to cover the surface of the cluster layer to minimize leakage current generated from the cluster layer. Figure 4 As shown in , it simultaneously acts as a kind of energy barrier and thus can adjust the overall electron mobility of the electron transport layer 150 to a suitable level and thus improve the charge carrier balance.
[0122] As described above, the electroluminescent device 10 according to the embodiment includes an inorganic layer 151 having a very high electron mobility and improving the luminous efficiency of the emission layer 140 including quantum dots, and an organic layer 153 that minimizes the leakage current due to the surface morphology of the inorganic layer 151 and simultaneously adjusts the overall electron mobility of the electron transport layer 150 to an appropriate level, and therefore, the electron transport layer 150 has a hybrid stacking structure of the inorganic layer 151 / organic layer 153.
[0123] Therefore, the electroluminescent device 10 according to the embodiment can improve the charge carrier balance and light extraction efficiency of the emission layer and also minimize the leakage current, and thus show excellent driving characteristics and lifespan characteristics.
[0124] A display device according to an embodiment including the electroluminescent device 10 is described below.
[0125] A display device according to an embodiment includes a substrate, a driving circuit formed on the substrate, and a first electroluminescent device, a second electroluminescent device, and a third electroluminescent device disposed on the driving circuit and spaced apart from each other at predetermined intervals.
[0126] The first to third electroluminescent devices have the same structure as the electroluminescent device 10, but the wavelengths of light emitted from the respective quantum dots may be different from each other.
[0127] In one embodiment, the first electroluminescent device is a red device that emits red light, the second electroluminescent device is a green device that emits green light, and the third electroluminescent device is a blue device that emits blue light. In other words, the first to third electroluminescent devices may be pixels in the display device that respectively exhibit red, green, and blue.
[0128] However, the embodiment is not necessarily limited thereto, but the first to third electroluminescent devices may respectively express magenta, yellow, cyan, or may express other colors.
[0129] One of the first to third electroluminescent devices may be the electroluminescent device 10. For example, the electroluminescent device displaying blue in the display device is the electroluminescent device 10 and the electroluminescent devices displaying red and green may include an electron transport layer composed of an organic layer or an inorganic layer or including both an organic layer and an inorganic layer, provided that the organic layer is directly formed on the emission layer. Alternatively, one of the first to third electroluminescent devices may be the electroluminescent device 10 and the rest may be electroluminescent devices including a fluorescent material or a phosphorescent material instead of quantum dots as light-emitting particles.
[0130] The substrate may be a transparent insulating substrate or may be made of a ductile material. The substrate may include glass or a polymer material in the form of a film having a glass transition temperature (Tg) greater than about 150° C. For example, it includes a material based on COC (cyclic olefin copolymer) or COP (cyclic olefin homopolymer).
[0131] The driving circuit is disposed on the substrate and is independently connected to each of the first to third electroluminescent devices. The driving circuit may include: at least one group of lines including a scan line, a data line, a driving power line, a common power line, etc., at least two thin film transistors (TFTs) connected to the lines and corresponding to one organic light emitting diode, and at least one capacitor, etc. The driving circuit may have various known structures.
[0132] As described above, the display device according to the embodiment may display an image with improved color purity and color reproducibility without a separate light source such as a backlight unit, and may particularly exhibit improved driving characteristics and lifespan characteristics.
[0133] Hereinafter, the embodiments are described in more detail with reference to Examples. However, these Examples are exemplary, and the present disclosure is not limited thereto.
[0134] Example 1
[0135] An ITO layer was deposited on a glass substrate as a first electrode (anode), and a PEDOT:PSS layer (hole injection layer) and a poly(9,9-dioctyl-fluorene-co-N-(4-butylphenyl)-diphenylamine) (TFB) polymer layer (hole transport layer) were separately and sequentially formed thereon by using a solution process. Subsequently, a blue emission layer was formed thereon by coating blue quantum dots (ZnTeSe) dispersed in an organic solvent and heat-treating it at 80°C for 30 minutes under a nitrogen atmosphere.
[0136] On the other hand, ZnO particles having an average particle diameter of 3 nm were washed three times and then formed into a ZnO cluster layer (inorganic layer) having a thickness of about 40 nm on the blue emission layer.
[0137] Subsequently, on the surface of the ZnO cluster layer, An organic compound 1 layer including an organic compound 1 (a phosphine oxide-based compound, NET218, Novaled Electron Transport material 218, obtained from Novaled) was formed to a thickness of 2 nm to 20 nm at a deposition rate of, and an Al layer was deposited thereon as a second electrode (cathode) to manufacture an electroluminescent device according to Example 1.
[0138] Example 2
[0139] An electroluminescent device was manufactured according to the same method as in Example 1, except that an organic compound 1 and an organic compound 2 (phosphonophenol-based compound, Novaled Co., NDN87, Novaled Dopant n-side material 87) in a weight ratio of 1:1 were co-deposited to form an organic compound 1:organic compound 2 blended layer instead of the organic compound 1 layer.
[0140] Example 3
[0141] An electroluminescent device was manufactured according to the same method as in Example 1, except that the ZnO cluster layer was formed to have a thickness of 20 nm.
[0142] Comparative Example 1
[0143] An electroluminescent device was manufactured according to the same method as in Example 1, except that an Al layer was formed directly on the ZnO cluster layer without forming the organic compound 1 layer.
[0144] Comparative Example 2
[0145] An electroluminescent device was manufactured according to the same method as in Example 1, except that an organic compound 1:ZnO blended layer was formed on the blue emission layer by washing ZnO particles having an average particle diameter of 3 nm two to three times and then mixing them with the organic compound 1 in a weight ratio of 20:1, and then an Al layer was deposited thereon.
[0146] Comparative Example 3
[0147] An electroluminescent device was manufactured according to the same method as Comparative Example 2, except that a ZnO:Organic Compound 2 blended layer was formed by mixing ZnO and Organic Compound 2 instead of Organic Compound 1 at a weight ratio of 20:1.
[0148] Comparative Example 4
[0149] An electroluminescent device was manufactured according to the same method as in Example 1, except that an Al layer was formed directly on the ZnO cluster layer without forming the organic compound 1 layer.
[0150] evaluate
[0151] First, the IVL characteristics of the electroluminescent devices according to Example 1 and Comparative Examples 1-3 are shown in Figure 5-7 and its JV characteristics are shown in Figure 8 middle.
[0152] Figure 5-7 are graphs showing IVL characteristics of the electroluminescent devices according to Example 1 and Comparative Examples 1-3; respectively, Figure 5 Display voltage-current density, Figure 6 Display voltage-brightness, and Figure 7 Display brightness - external quantum efficiency (EQE).
[0153] Reference Figure 5 and 6 , Example 1 shows low current density at the same voltage and low luminance at the same voltage compared to Comparative Examples 1 and 2, and the reason is that the organic compound 1 layer acts as an energy barrier and reduces the current density at low voltage.
[0154] However, referring to Figure 7 Compared with Comparative Examples 1-3, Example 1 has a brightness of less than or equal to about 1000 cd / m 2 In particular, Example 1 shows very excellent external quantum efficiency at a brightness of about 100 cd / m 2 In addition, compared with Comparative Examples 1-3, Example 1 shows a smaller decrease in external quantum efficiency in a high brightness region at a high voltage and thus shows stable driving characteristics.
[0155] In other words, since the organic compound 1 layer is further formed on the ZnO cluster layer and thus the organic compound 1 layer acts as an energy barrier against the movement of electrons from the Al layer to the ZnO cluster layer, Example 1 shows a slight decrease in current density and brightness, but shows very excellent luminous efficiency at low brightness.
[0156] On the other hand, compared with Example 1 and Comparative Example 2, Comparative Example 3 shows low current density at the same voltage, low luminance at the same voltage, and low external quantum efficiency at the same luminance, and these results are expected to depend on the difference in organic semiconductor materials.
[0157] Figure 8 is a graph showing the voltage-current density relationship of the electroluminescent devices according to Example 1 and Comparative Examples 1-3. Figure 8 is a graph showing current density with a y-axis on a logarithmic scale.
[0158] Reference Figure 8 , compared with Comparative Example 1 including only a ZnO cluster layer, Example 1 had an inorganic-organic hybrid stacked structure by further forming an organic compound 1 layer on the surface of the ZnO cluster layer and thus showed a leakage current reduction effect of about 1000 times.
[0159] On the other hand, when the electroluminescent intensity with respect to the wavelength was examined with respect to the electroluminescent device of Example 1, the electroluminescent device of Example 1 showed a narrow full width at half maximum (FWHM) of about 28 nm.
[0160] The time-dependent brightness reduction of the electroluminescent devices according to Example 2 and Comparative Examples 1 and 2 was measured, and the results are shown in Fig. 9 middle.
[0161] Fig. 9 1 is a time-luminance graph of the electroluminescent devices according to Example 2, Comparative Example 1, and Comparative Example 2.
[0162] Reference Fig. 9 , the electroluminescent device of Example 2 showed a slow decrease in brightness compared with those of Comparative Examples 1 and 2, and when T 50 When T is defined as the time elapsed when the electroluminescent device shows a brightness of 50% relative to the initial brightness (100%), Example 2 shows the longest T of 1.42 hours. 50 , Comparative Example 1 showed a T of 0.27 hours 50 , and Comparative Example 2 showed a T of 0.74 hours 50 .
[0163] As the leakage path due to the surface morphology of the ZnO cluster layer increases, the life characteristics decrease, and therefore, compared with Comparative Examples 1 and 2, Example 2 including an organic compound 1:organic compound 2 blended layer that covers and minimizes the leakage path of the ZnO cluster layer shows excellent life characteristics.
[0164] On the other hand, the IVL characteristics of the electroluminescent devices of Example 3 and Comparative Example 4 are shown in Figure 10-12 and the JV characteristics are shown in Fig.13 middle.
[0165] Figure 10-12 are graphs showing IVL characteristics of the electroluminescent devices according to Example 3 and Comparative Example 4; respectively, Fig.10 Display voltage-current density, Fig.11 Display voltage-brightness, and Fig.12 Display brightness - external quantum efficiency.
[0166] Reference Figure 10-12 Example 3 shows a slightly lower current density at the same voltage and a slightly lower brightness at the same voltage due to the organic compound 1 layer acting as an energy barrier against electrons moving from the Al layer to the ZnO cluster layer, but shows a brightness of less than or equal to about 500 cd / m 2 Very high external quantum efficiency at low brightness, and especially less than or equal to about 100 cd / m 2 Very high external quantum efficiency of about 2.6% at low brightness.
[0167] Fig.13 3 is a voltage-current density diagram of the electroluminescent devices according to Example 3 and Comparative Example 4. Fig.13 is a graph showing current density with a y-axis on a logarithmic scale.
[0168] Reference Fig.13 , compared with Comparative Example 4 having only a ZnO cluster layer, Example 3 further having an organic compound 1 layer on the surface of the ZnO cluster layer exhibited an excellent leakage current reduction effect.
[0169] While the present disclosure has been described with respect to what are presently considered to be practical example embodiments, it will be understood that the invention is not limited to the disclosed embodiments, but rather is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0170] <Description of symbols>
[0171] 10: Electroluminescent device 100: Substrate
[0172] 110: first electrode 120: hole injection layer
[0173] 130: hole transport layer 140: emission layer
[0174] 141: Luminescent particles 150: Electron transport layer
[0175] 151: Inorganic layer 151a: Surface area
[0176] 152: Inorganic nanoparticles
[0177] 152a: Inorganic nanoparticles in the surface region
[0178] 153: organic layer 160: second electrode
Claims
1. An electroluminescent device comprising a first electrode and a second electrode facing each other; an emission layer disposed between the first electrode and the second electrode and comprising a plurality of light-emitting particles; a hole transport layer disposed between the first electrode and the emission layer; as well as An electron transport layer is provided between the emission layer and the second electrode, The electron transport layer comprises an inorganic layer disposed on the emitting layer and comprising a plurality of inorganic nanoparticles; and an organic layer disposed directly on at least a portion of an upper surface of the inorganic layer on a side opposite to the emission layer, wherein the organic layer has a lowest unoccupied molecular orbital energy level of -2.3 eV to -1.8 eV, and The organic layer acts as an energy barrier against electrons moving from the second electrode to the inorganic layer. wherein the inorganic layer is disposed on the emission layer as a cluster layer including the plurality of inorganic nanoparticles, The surface of the cluster layer includes a surface region having two or more grains each including the inorganic nanoparticles, wherein a grain boundary is formed between adjacent grains, and The organic layer fills at least a portion of the grain boundary.
2. The electroluminescent device of claim 1, wherein the organic layer completely covers a surface of the inorganic layer between the inorganic layer and the second electrode. 3 . The electroluminescent device of claim 1 , wherein the organic layer has a lowest unoccupied molecular orbital energy level of −2.2 eV to −1.8 eV.
4. The electroluminescent device according to claim 1, wherein the organic layer has 10 -3 cm 2 / V·s-10 -1 cm 2 / V·s electron mobility.
5. The electroluminescent device of claim 1, wherein the inorganic nanoparticles comprise ZnO, TiO2, ZrO2, SnO2, WO3, Ta2O3, or a combination thereof. The electroluminescent device according to claim 1 , wherein the average particle diameter of the inorganic nanoparticles is less than or equal to 150 nm.
7. The electroluminescent device of claim 1, wherein the cluster layer is disposed directly on the emissive layer.
8. The electroluminescent device of claim 1, wherein the organic layer comprises an organic semiconductor compound, and the organic semiconductor compound is a quinolone-based compound, a triazine-based compound, a quinoline-based compound, a triazole-based compound, a naphthalene-based compound, or a combination thereof.
9. The electroluminescent device of claim 8, wherein the organic layer comprises at least two different organic semiconductor compounds.
10. The electroluminescent device of claim 9, wherein The organic layer includes a first organic semiconductor compound and a second organic semiconductor compound different from each other, and The weight ratio of the first organic semiconductor compound to the second organic semiconductor compound in the organic layer is 3:7-7:
3. The electroluminescent device according to claim 1 , wherein the average thickness of the organic layer is 2 nm to 20 nm. 12 . The electroluminescent device of claim 1 , wherein the inorganic layer and the organic layer are alternately stacked two or more times.
13. The electroluminescent device of claim 1, wherein the plurality of light-emitting particles comprises quantum dots.
14. The electroluminescent device of claim 13, wherein the quantum dots comprise: A Group II-VI compound excluding Cd, a Group III-V compound, a Group IV-VI compound, a Group IV element or compound, a Group I-III-VI compound, a Group I-II-IV-VI compound excluding Cd, or a combination thereof.
15. The electroluminescent device of claim 13, wherein the quantum dots have a core-shell structure.
16. The electroluminescent device of claim 1, wherein the electron transport layer has no electroluminescence.
17. A display device comprising the electroluminescent device according to any one of claims 1 to 16.
Citation Information
Patent Citations
Water-cooled egr cooler
KR1020180028836A
OLED (Organic Light-Emitting Diode) and fabrication method thereof
CN104134754A
Organic light-emitting diode
US20140353596A1
Organic light-emitting diode and display panel including the same
US20160149150A1
Quantum dot LED and OLED integration for high efficiency displays
US20170221969A1